2011
DOI: 10.1007/s10842-011-0117-2
|View full text |Cite
|
Sign up to set email alerts
|

Competition Effects in a Liberalized Railway Market

Abstract: This paper presents a game-theoretic model of a liberalized railway market, in which train operation and ownership of infrastructure are vertically separated. We analyze how the regulatory agency will optimally set the charges that operators have to pay to the infrastructure manager for access to the tracks and how these charges change with increased competition in the railway market. Our analysis shows that an increased number of competitors in the freight and/or passenger segment reduces prices per kilometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The second result is global consensus about the benefit for users in terms of frequency and price. Theoretically, competition should have a positive effect on social welfare by increasing frequency and reducing price (Lang et al, 2013;Feuerstein et al, 2018;Broman and Eliasson, 2019). Empirically, the effect is clear on frequency.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The second result is global consensus about the benefit for users in terms of frequency and price. Theoretically, competition should have a positive effect on social welfare by increasing frequency and reducing price (Lang et al, 2013;Feuerstein et al, 2018;Broman and Eliasson, 2019). Empirically, the effect is clear on frequency.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Such studies are given, for example, in [7]. The material accumulated to date makes it possible to build mathematical models based on game theory that describe the relationship between participants in the rail transportation market, as, for example, in the paper by Lang, et al [9]. At the same time, less attention is devoted to the problem of interaction between railway infrastructure fa cilities of different owners in a competitive market.…”
Section: Information Technologies Systems Analysis and Administrationmentioning
confidence: 99%
“…Some authors did consider the pricing of infrastructure when there is intramodal competition. For instance, Lang et al (2013) investigated the impact of the number of operators on the access charge using a game theoretic model, and found that an increase in the number of operators leads to a higher access charge. For air transport, Verhoef (2010) studied airport congestion pricing in case of asymmetric airlines and found that the least efficient airline quits under differentiated charging.…”
Section: Infrastructure Pricing In Air Transport and Hsrmentioning
confidence: 99%